O papel do design no desenvolvimento motor das crianças - Oliveira, Regina Salnikova, 1985- (2015)
This research called “The Role of Design in the Motor Development of Children” aims at creating a type of intervention in sports equipment for children between two and five years old. The equipment proposed will be inserted in the child’s home, where there is less supply and where the child spends most of his or her time. The aim of this study is to find out how a toy design project can encourage children to have and enjoy more physical activity. Thus a survey was made concerning toys and the act of playing as it takes up most of a child’s time. In order to go deeper in the knowledge of toys in general a historical study was made as well as some research regarding the national and the international market in this business. Modes of toy classification were also discussed in order to analyze more precisely the case studies and this particular project. The physical and psychological capabilities of each age between 0 and 5 years were considered in order to assess the child’s intellectual abilities and behaviour in his or her early years. The interviews with paediatricians and parents made it possible to get to know the real needs and concerns in a child’s physical development. We therefore made a study of sports equipment for indoor and outdoor spaces in old times and nowadays. Thus comparing various types of sports equipment it was possible to confirm the existence of a business niche, an opportunity of intervention in the child’s home, with a product for which there is short supply in the market. Finally we present the project proposal, the sports equipment we called the “Tree”. It aims at developing the physical abilities of children and at promoting a healthy and active life later on